Analisis Penegakkan Hukum Pidana Internasional di Dunia Modern - Putri Dewi Wiji Lestari; Zaenudin Zaenudin; Arman Sanun (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
International criminal law is a crucial instrument within the international legal system designed to address serious crimes that transcend national jurisdiction, such as genocide, war crimes, and crimes against humanity. International criminal law serves as a means to uphold justice, maintain international order, and prevent impunity for perpetrators of serious crimes that have a broad impact on the global community. This study aims to examine the enforcement of international criminal law in the modern era, emphasizing law enforcement mechanisms and the role of cooperation between states and international institutions. The research method used is normative juridical research, with an approach to relevant laws and regulations, legal doctrine, and court decisions. The results indicate that the effectiveness of international criminal law enforcement still faces various obstacles, primarily stemming from state political interests, weak commitment to international cooperation, and inconsistencies between legal norms and their implementation. The principle of complementarity is a fundamental element of this system, as it positions states as the primary actors in the prosecution process, while international judicial institutions play a complementary role if national mechanisms are ineffective. Furthermore, harmonization of national laws with international criminal law provisions and strengthening cross-border cooperation are determining factors in the success of law enforcement. This study concludes that synergy between states and international institutions, accompanied by strong political commitment, is a key prerequisite for the realization of a just and sustainable international criminal law enforcement system.